2005
DOI: 10.1007/s10569-004-2415-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Evolution of Orbits About A Precessing Oblate Planet: 1. The Case of Uniform Precession

Abstract: It was believed until very recently that a near-equatorial satellite would always keep up with the planet's equator (with oscillations in inclination, but without a secular drift). As explained in Efroimsky and Goldreich (2004), this misconception originated from a wrong interpretation of a (mathematically correct) result obtained in terms of non-osculating orbital elements. A similar analysis carried out in the language of osculating elements will endow the planetary equations with some extra terms caused by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 44 publications
0
48
0
Order By: Relevance
“…This result, proven by Efroimsky (2005b), is valid only in the case of uniform precession and only for a solitary satellite, in the absence of any other disturbances (like the gravitational pull of the Sun or of another satellite). However, numerical simulation has shown that even in realistic situations of variable precession, the deviations between the secular parts of the contact and the corresponding osculating elements accumulate very slowly, for a solitary satellite (Gurfil et al, 2006).…”
Section: Definitionsmentioning
confidence: 90%
See 1 more Smart Citation
“…This result, proven by Efroimsky (2005b), is valid only in the case of uniform precession and only for a solitary satellite, in the absence of any other disturbances (like the gravitational pull of the Sun or of another satellite). However, numerical simulation has shown that even in realistic situations of variable precession, the deviations between the secular parts of the contact and the corresponding osculating elements accumulate very slowly, for a solitary satellite (Gurfil et al, 2006).…”
Section: Definitionsmentioning
confidence: 90%
“…Kinoshita (1993) studied the motion of a satellite relative to the equatorial plane of its oblate parent parent, and Rubincam (2000) discusses the possibility that Pluto may be in "precession-orbit" resonance. Expressions for the precession contribution to the disturbing function are given implicitly by Goldreich (1965b) and explicitly by Kopal (1969), Brumberg et al (1970) and Efroimsky (2005b); using their results, we can write:…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, according to (9 -10), the Cartesian components of the velocity in the precessing equatorial frame will be given by g ( C , t ) + ∂∆H precess /∂ p . However, since the second term of this sum is equal to − µ × r , then g ( C , t ) turns out to always render the velocity with respect to the inertial frame of reference (Efroimsky & Goldreich 2004, Efroimsky 2005). …”
Section: A 13 Calculation Of the Angular Velocities Via The Andoyer mentioning
confidence: 99%
“…Instead, we must use (9) with the substitution (12). This generic rule applied both to orbital and rotational motions.…”
mentioning
confidence: 99%
See 1 more Smart Citation